1993
DOI: 10.1254/jjp.63.209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Motor-Stimulating Action of EM523, an Erythromycin Derivative, and Prostaglandin F2 in Conscious Dogs

Abstract: ABSTRACT-The effect of , an erythromycin derivative, on gastrointestinal motility was investigated using conscious dogs in the fasting state, and it was compared with those of motilin and prostaglandin F2a (PGF2a). EM523 and motilin given as i.v. infusions induced strong contractions in the stomach that migrated along the intestine. On the other hand, PGF2a stimulated intestinal contractions, but its effect on gastric motility was weak. EM523 had 1/50 the potency of motilin and 6 times the potency of PGF2a for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Similar results in conscious dogs have been demonstrated that low dose motilin (0.2 μg/kg/hr, i. v. infusion) only increased gastric antral motility; more than 5 times higher doses of motilin were required to increase colonic motility in the interdigestive state (Shibata et al, 1995). Inatomi et al (1993) also reported that EM-523, one of the EMA derivatives, administered i. v. infusion at 30 μg/kg/h could induce stronger MMC-like contractions in the gastric antrum, but failed to induce colonic motor activity in conscious dogs. There may be a difference in sensitivity to motilin and motilin receptor agonists between the gastric antrum and the colon in dogs.…”
Section: Discussionsupporting
confidence: 69%
“…Similar results in conscious dogs have been demonstrated that low dose motilin (0.2 μg/kg/hr, i. v. infusion) only increased gastric antral motility; more than 5 times higher doses of motilin were required to increase colonic motility in the interdigestive state (Shibata et al, 1995). Inatomi et al (1993) also reported that EM-523, one of the EMA derivatives, administered i. v. infusion at 30 μg/kg/h could induce stronger MMC-like contractions in the gastric antrum, but failed to induce colonic motor activity in conscious dogs. There may be a difference in sensitivity to motilin and motilin receptor agonists between the gastric antrum and the colon in dogs.…”
Section: Discussionsupporting
confidence: 69%
“…An alternative, not exclusive to the direct action of erythromycin, is that the central action of erythromycin is not related to erythromycin itself but to another factor. It has been suggested that the final nervous pathway for erythromycin derivative (EM-523) might involve facilitation of serotoninergic transmission (18,31). A similar regulation has also been demonstrated for motilin (20).…”
Section: Discussionmentioning
confidence: 78%
“…It has been previously reported [16][17][18] that injection or infusion of motilin (0.1-1.0 Ìg/kg) induced phase III contractile activity in the gastric antrum. Moreover, we reported earlier [4] that SK-896 and human motilin bind the rabbit gastroduodenal motilin receptor with equal ability and that the 50% inhibitory concentrations for binding of 125 I-motilin to this receptor were 3.5 B 1.5 and 3.1 B 1.8 nmol/l, respectively.…”
Section: Discussionmentioning
confidence: 93%